Government Policy in Public Services in the Republic of Tatarstan, Russia - Refly Setiawan; Mohamad Fikri Sulthan; Abdurrahman Abdurrahman (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractGovernment policy is a step taken by the government to achieve a goal. The main objective of the policy of the Republic of Tatarstan is to provide the conditions for the full social and cultural development of the whole society, to strengthen civil society and society's morals on the basis of respect for the rights of citizens and their recognition as the highest value. This study aims to explain how government policies are related to public services and to find out how the government of the Republic of Tatarstan provides the best services for the welfare of the people. This research uses qualitative research methods with a descriptive approach. The results of this study explain that the government has taken the right policy steps in providing services to the community, namely by providing fast, responsive, optimal, fair, transparent service and utilizing technological advances for the welfare of the people in the Republic of Tatarstan.Keywords: Government Policy, Public Service, Republic of Tatarstan AbstrakKebijakan pemerintah merupakan suatu langkah yang diambil oleh pemerintah untuk tercapainya suatu tujuan. Tujuan utama dari kebijakan Republik Tatarstan adalah untuk menyediakan kondisi bagi perkembangan sosial dan budaya-budaya penuh seluruh masyarakat, untuk memperkuat masyarakat sipil dan moral masyarakat atas dasar penghormatan pada hak-hak yang di miliki warga negara serta pengakuannya sebagai nilai tertinggi. Penelitian ini bertujuan untuk menjelaskan bagaimana Kebijakan pemerintah terkait dengan pelayanan publik dan untuk mengetahui bagaimana pemerintah dalam memberikan pelayanan bagi kesejahteraan seluruh masyarakat. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif. Hasil penelitian ini menjelaskan bahwa pemerintah Republik Tatarstan telah mengambil langkah kebijakan yang tepat dalam pelayanan kepada masyarakat yaitu dengan pelayanan yang cepat, tanggap, optimal, adil, transparan, dan memanfaatkan kemajuan teknologi demi kesejahteraan masyarakat di Republik Tatarstan.Kata Kunci: Kebijakan Pemerintah, Pelayanan Publik, Republik Tatarstan АннотацияПравительственная политика - это шаг, сделанный правительством для достижения цели. Основная цель политики Республики Татарстан - обеспечение условий для полноценного социального и культурного развития всего общества, укрепление гражданского общества и нравственности общества на основе уважения прав граждан и признания их высшее значение. Это исследование призвано объяснить, как политика правительства связана с государственными услугами, и выяснить, как правительство Республики Татарстан предоставляет лучшие услуги для благосостояния людей. В этом исследовании используются качественные методы исследования с описательным подходом. Результаты этого исследования объясняют, что правительство предприняло правильные политические шаги по предоставлению услуг населению, а именно путем предоставления быстрых, оперативных, оптимальных, справедливых и прозрачных услуг и использования технологических достижений на благо людей в Республике Татарстан.Ключевые слова: государственная политика, государственная служба, Республика Татарстан